PENGARUH JENIS BAHAN ORGANIK DAN KONSENTRASI PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU (Phaseolus radiatus L.)â€ - Renasari, Novita -; -, Priyono -; Ariyantoro, Hadi - (Innofarm:Jurnal Inovasi Pertanian, 2013)
The research on :"The Effect of Material Type and Concentration Organic Liquid Organic Fertilizer and Crop Growth Of Green Beans (Phaseolus radiatus L.)" was held from 6th April 2013 to date 22th Juny 2013 at the Experimental Garden of the Faculty of Agriculture, University Slamet Riyadi which is located in the Village Kadipiro, Subdistrict Banjarsari, Town Surakarta. This research uses the basic design of RGD (completely randomized design) are arranged in a factorial with 2faktor treatments and 3 replications. Data were analyzed using analysis of Variety, followed by Test Honestly Significant Difference (HSD) at 5% significance level. The results of research show that, 1) type of organic matter is the best manure, because it can increase the yield of green bean plants are optimally weight of 100 seeds on average 5.33 g per crop and pod yield an average of 19.68 g, 2) best LOF was 10 cc / l of water, because it can increase the yield of green bean crop that optimal weight of 100 Â seeds on average 5.36 g per crop and pod yield an average of 19.67 g, interaction best treatment is a combination of LOF concentration of 15 cc / l of water with rice husk (4 branches per crop. Key words : Material Organic, Organic Liquid Organic Fertilizer,Â  Green Beans